A multi‐layer framework for energy efficiency assessment of shore‐to‐ship fast charging systems including onshore batteries - Siamak Karimi; Mehdi Zadeh; Jon Are Suul (IET Electrical Systems in Transportation)
Abstract This paper proposes a three‐layer framework for energy efficiency evaluation of Shore‐to‐Ship Charging (S2SC) systems using load‐dependent loss models of the components. The considered S2SC system is supplied by the grid but is also supported by On‐Shore Batteries (OSB). The presented approach is then used to investigate the impact of the specific design and operational parameters on energy efficiency. Power system architectures for three general S2SC solutions for ac, dc, and inductive charging are defined and compared in terms of energy efficiency. Operational parameters are also considered in the analysis, namely, the grid power ratio, determining the load sharing between the grid and the OSB, as well as the OSB charging profile. A case study is performed with peak charging power of 1 MW, and the most efficient S2SC solutions are identified for both ac‐ and dc‐based onboard power systems. Moreover, it is shown that charging OSB with the highest available power from the grid between the charging breaks would often lead to higher energy efficiency than the maximum utilization of the available charging time. Field data from a real S2SC system is used to verify the estimated energy efficiency by the proposed framework. The analysis of the real case S2SC is then extended to include and verify a projected OSB.